Covid-19 e didattica a distanza.Il caso Basilicata, una regione a rischio digital divide - Marcella De Filippo; Annalisa Percoco; Angela Voce (Fondazione Eni Enrico Mattei (FEEM), 2020)
– This paper presents the implications that Covid-19 has had on educational systems as a result of the application of social distancing measures imposed on people by the governments of each individual country. The lockdown has accelerated digitalization but has also shown the internal weaknesses and fragilities of states. Distance learning (DAD) has been the response of schools to the suspension of lessons in order to guarantee students' right to education. The working paper explains what DAD is and also presents some data, collected by the major international and national organizations, on the level of digitization of the Italian school; it then explores digital education in Lucanian schools through the analysis of statistical sources and literature available and through the questionnaire administered in CAWI modality to a sample of teachers in Lucania. The field survey studies the current condition of infrastructures and the digital literacy of teachers, with a specific focus on the management of the emergency phase, in order to draw policy indications and useful ideas for a new programming stage that will be able to take advantage of all the new opportunities created within the pandemic. To conclude our argumentation, we outline some of the good practices present in Basilicata, which for several years now has been experimenting with special innovative educational activities that arise from forms of business social responsibility. Projects promoted by companies to support the innovation of the school system represent a strategic investment for market competitiveness and economic development. Ensuring quality, fair and inclusive education is the fourth goal of the UN Agenda 2030 and is a fundamental one for the welfare of both individuals and societies. Investing in education, in the medium and long term, will reduce inequalities and lead to the economic, cultural and social change that is necessary for the prosperity of people and the Planet and for the realization of new models of sustainable development.
Keywords: Q4; Q41; O13; 330; Covid 19; Digitalization; Technology; Education; Distance learning; SDGs; Basilicata